(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Manju Kapur’s novel Difficult Daughters is an account of a little girl’s voyage again into her mom’s agonizing past. It traverses the class of fiction and history and falters in both. The fantasy of independence and decolonization were portrayed unmistakably. The occurrences like bashes of assault and murder, organized for the sake of opportunity. First, Ida, the storyteller and girl of hero, attempting to recover her mom’s mystery life, ends up being fundamental story. Virmati was an offspring of a moderate Hindu family, becomes an adult in the fierce and idealistic 1040s. It was viewed as the season of change to the informed Indians. Presented to taste the new wine of opportunity, Virmati experiences opportunity contenders all things considered and influences, becomes hopelessly enamored, and weds an officially hitched teacher. Sequestered with relative, co-spouse and stepchildren, Virmati uses propelled training as a departure course. It is valid here, Training prompted independence and free direct. Her advancement parallels the recently discovered opportunities of taught Indian ladies, however twofold principles win, expanding familiarity with the ties that predicament. This paper draws out the mother – girl connections in the novel. In the contemporary society one of the most recent consuming issues is, different crisis in the family. Today the two people stick to free present day way of life thus, they would rather not live under conjugal rooftop. Both are additionally conscious of their own salvation and individuality, so to accomplish an autonomous status they break the conjugal standards and rushed to look for their underlying foundations. Thusly, the principle goal of this conceptual paper is to bring out how Manju Kapur, an extraordinary Indian artistic author has drawn out the issue of the present marriage, with particular reference to her novel Difficult Daughters.